Mathematics at Kaunas university in 1940–1950 - Pekarskas, Vidmantas; Pekarskienė, Aldona (Lietuvos matematikos rinkinys, 1998)
The activity of mathematicians at Kaunas university during the period of 1940–1950 before the abolition of Kaunas university and founding of Kaunas polytechnical institute is investigated in this article.